Glosematic Rhetoric Construction on the Language Discourse of High School Students - Sri Wahyuni; Ida Zulaeha; Subiyantoro Subiyantoro; Hari Bakti Mardikantoro (Universitas Negeri Semarang, 2021)
The purpose of this study was to find out the formula for the expression and content of glosematic rhetoric of linguistic discourse of high school students and the factors behind the expression and content of rhetoric. This research is qualitative descriptive research and the object of research is student discourse Senior High School. The data of this study are fragments of the linguistic discourse of students in grades X, XI, and XII in Indonesian subjects in terms of the construction of glossary rhetoric, while the data sources are linguistic texts in the form of expositions, arguments, explanations, editorials, and articles. Data collection is done by listening techniques and advanced techniques in the form of note-taking techniques. The results of this study are the formulas of glosematic rhetorical expressions of linguistic discourse for high school students in the form of processibility principles, principles of clarity, economic principles, expressivity principles, appreciative principles, ethos logos, pathos, forensic rhetoric, experiential values, relational, expressive, dynamic modalities, intentional, epistemic. , and deontic. The formula for the content of the glossary rhetoric found is in the form of exposition and argumentation to inform. Expression and content in essay discourse are influenced by linguistic factors 88.6% and non-linguistic factors 45.7%. The linguistic factor is influenced by morphology 74.3% and syntax 68.6%. Morphological factors occur because of the affixing process 74.3%, compounding 71.4%, and repetition 51.4% while the syntactic factor occurs due to the use of active sentences 68.6%, complex sentences 57.1%, simplex sentences 48.6%, and passive voice 42.9%. Non-language factors are influenced by time 65.7%, environment 62.9%, social 42.9%, place 40%, and connotation 28.6%. 4% while the syntactic factor occurs because of the use of active sentences 68.6%, complex sentences 57.1%, simplex sentences 48.6%, and passive sentences 42.9%. Non-language factors are influenced by time 65.7%, environment 62.9%, social 42.9%, place 40%, and connotation 28.6%. 4% while the syntactic factor occurs because of the use of active sentences 68.6%, complex sentences 57.1%, simplex sentences 48.6%, and passive sentences 42.9%. Non-language factors are influenced by time 65.7%, environment 62.9%, social 42.9%, place 40%, and connotation 28.6%.